MANAGEMENT OF DYSPNEA IN PALLIATIVE CARE: EXPERIENCE REPORT ON THE STRUCTURING OF AN EDUCATIONAL VIDEO - Almeida, Vanessa Albuquerque Vilaça de (2024)
Palliative care aims to enhance the quality of life for patients and their families facing life-threatening illnesses by effectively managing signs and symptoms. This approach addresses physical, emotional, social, and spiritual well-being. Among the most frequently reported symptoms by these patients is dyspnea, which also stands as a common cause for emergency service visits, profoundly affecting the quality of life of both patients and their families. The objective of the study is to develop an educational video that guides patients and caregivers on the management of dyspnea in palliative care. This study is descriptive in nature and employs a methodological approach to the experience of creating an educational video using the CTM3 method. Literature suggests that educational resources are crucial in the teaching-learning process, particularly in health education. Educational videos, being an attractive and easily understandable technology, can significantly enhance the educational process. This report aims to facilitate the creation of additional educational resources, promoting knowledge dissemination and fostering behavioral changes that enhance care adherence. Ultimately, it seeks to improve the safety and comfort of both patients and their caregivers.